Cross-Cultural Communication and The Hippy Trail 1957–78. Issue 5 (4th July 2017) - Gemie, Sharif
Abstract : The hippy trail flourished in the 1960s: it was one of the most dramatic examples of the values of the counter-culture. This essay first presents a sociological sketch of typical travellers, and then considers how ordinary hippy trail travellers interacted with local people. It compares the attitudes of hippy trail travellers with the classical model of Orientalism, and notes that the travellers largely distanced themselves from imperialist culture. The essay establishes that there were a variety of reactions by travellers to their experience, ranging from racism, through fear, shyness and romanticization, to attempts to create reasonably egalitarian forms of cross-cultural communication.